Modern Aspects of Etiology and Pathological Anatomy of Renal Cancer (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
This article presents a literature review of modern aspects of the etiology and pathological anatomy of kidney cancer.